2006
DOI: 10.1509/jmkg.70.3.021
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cognition and Affect in the Formation of Customer Satisfaction: A Dynamic Perspective

Abstract: Despite the strong recognition that customer satisfaction should be viewed from a dynamic perspective, little is known about how the satisfaction judgment develops over time. Therefore, this study provides a dynamic analysis of the simultaneous influence of cognition and affect in the satisfaction formation process. The results of an experimental study based on a real consumption experience indicate that the impact of cognition on the satisfaction evaluation increases and the influence of affect decreases over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
0
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(150 citation statements)
references
References 69 publications
10
125
0
15
Order By: Relevance
“…Examining both knowledge and taste has the potential to provide a richer and more complete understanding of consumer behavior, particularly in product and service categories where there are strong elements of aesthetics. This view is in line with a current stream of research on the importance of hedonic aspects in consumption (e.g., Babin et al 1994;Batra and Ahtola 1991;Homburg et al 2006). Batra and Ahtola (1991), p. 159), for example, note that "consumers purchase goods and services and perform consumption behaviors for two basic reasons: (1) consummatory affective (hedonic) gratification (from sensory attributes), and (2) instrumental, utilitarian reasons concerned with 'expectations of consequences' (of a means-end variety, from functional and nonsensory attributes)."…”
Section: Taste and Its Subjective Versus Objective Basis Of Assessmentsupporting
confidence: 85%
“…Examining both knowledge and taste has the potential to provide a richer and more complete understanding of consumer behavior, particularly in product and service categories where there are strong elements of aesthetics. This view is in line with a current stream of research on the importance of hedonic aspects in consumption (e.g., Babin et al 1994;Batra and Ahtola 1991;Homburg et al 2006). Batra and Ahtola (1991), p. 159), for example, note that "consumers purchase goods and services and perform consumption behaviors for two basic reasons: (1) consummatory affective (hedonic) gratification (from sensory attributes), and (2) instrumental, utilitarian reasons concerned with 'expectations of consequences' (of a means-end variety, from functional and nonsensory attributes)."…”
Section: Taste and Its Subjective Versus Objective Basis Of Assessmentsupporting
confidence: 85%
“…However, limited studies focusing the effect of cognitive experience that consumers have during the process were encountered. In spite of this, the results of the study on web search and satisfaction context indicate that the cognitive experience that individuals have obtained has significant effects on the information search process (Homburg, Koschate, & Hoyer, 2006). When the level of consumers' information satisfaction is considered as the total of both objective and subjective experiences within the process (Al-Maskari & Sanderson, 2010;Dholakia & Bagozzi, 2001;Oliver, 1993Oliver, , 1997, the fact that research mostly focuses on objective variables effects yet there are limited studies on the effects of cognitive experience on online information satisfaction stands out as an important gap in the literature.…”
Section: Introductionmentioning
confidence: 85%
“…Previous literature indicates that product experience generates stronger behavioral beliefs and attitudes than indirect information such as advertising, and that it yields a higher level of attitude-behavior consistency (e.g., Fazio & Zanna, 1978;Homburg et al, 2006;Smith & Swinyard, 1983). Moreover, direct experience leads to the formation of behavior intention, which is readily accessible in the memory, resulting in a stronger relationship between attitudes and behavior intention (Fazio & Zanna, 1978).…”
Section: Literature Review On the Role Of Direct Experiencementioning
confidence: 99%
“…It has been noted that it is important to understand the sequence of activities that leads to the initial adoption and subsequent continued usage of a product or service (Karahanna et al, 1999;Kim, Choi, & Han, 2009). Previous studies have demonstrated that customers have different decision criteria toward a product or service at different stages (e.g., Homburg, Koschate, & Hoyer, 2006;Kim & Malhotra, 2005;Venkatesh, Morris, Davis, & Davis, 2003). From the perspective of a provider of MDS, understanding the relative influence of the antecedents on adoption and continued usage helps a manager better target investment and marketing for each group.…”
Section: Introductionmentioning
confidence: 99%